Innovating for a cause: the work and learning required to create a new approach to healthcare for homeless people. Issue 3 (3rd April 2018) - Fuller, Alison; Halford, Susan; Lyle, Kate; Taylor, Rebecca; Teglborg, Anne-Charlotte
Abstract: Innovation occupies a pivotal place in our understanding of knowledge-based economies, and this is raising questions about sources of innovation, how it originates, and the role played by employees, work practices and learning. This paper explores these issues through case study research into a new approach to providing healthcare for homeless people in England, and by bringing together conceptual insights from the employee-driven innovation literature, and more broadly from social and practice-based learning theory and organisational theory. Applying these perspectives to our case enables illumination of the innovation as a process – not an event – and as an ongoing set of organisational practices that transcend their origins. Through our analysis we argue that the notion of 'a cause' is helpful in elucidating the impetus and the commitment to making the innovation happen (and go on happening). Our findings are presented under three themes: 'establishing a cause', 'organising for innovation', and 'innovative capability in practice'. Building on these, we have identified five key inter-related dimensions which help conceptualise the work and learning that it took to create and (re-)enact the innovation and that we suggest may have relevance for understanding and characterising other employee-led innovations in and perhaps beyond healthcare.